Asymmetrical friction damper to improve seismic behavior of tension-only braces: An experimental and analytical study. (1st April 2022) - Gu, Zi; Lu, Wensheng; Gao, Yuqing
Highlights: Existing dissipators of tension-only braces are prohibited in China. A new passive mechanical device, namely asymmetrical friction damper (AFD), was designed, fabricated and tested. An asymmetrical constitutive model is proposed. Equal energy dissipation capacity principle is chosen to modify parameters. AFD co-works well with slender braces under different levels of earthquake. Abstract: In this paper, a passive asymmetrical friction damper (AFD), which significantly improves the hysteretic behavior of tension-only braces (TOBs) is introduced. The AFD carries force and dissipates energy under tensile loading and carries nearly zero force under compressive loading without causing TOB slackness. As a result, the AFD prevents the TOBs from buckling and from the impact seen in systems with significant slackness. In this study, twelve tests were conducted. Based on the results, an asymmetrical constitutive model was proposed to describe the mechanical properties of the AFD. In addition, to optimize model parameters, an equal energy method was proposed and verified. Furthermore, nonlinear time history analysis was operated on a six-story benchmark model with comparisons between the AFDs and fluid viscous dissipators (FVDs) systems. With the maximum reduction of 58.1% on the 5th floor and an average 23.8% reduction over six floors under the rare earthquake, the displacement-dependent as well as velocity-dependent AFD proved itself better performance in energy dissipation and making the building deform evenly to redistribute the internal force and avoid local failure.